Eliminating xenobiotics organic compounds from greywater through green synthetic nanoparticles - Heshammuddin, Nurul.Atikah; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Khamidun, Mohd Hairul (ELSEVIER, 2023)
Xenobiotic Organic Compounds (XOCs) have been widely considered to be pollutant compounds due to their harmful impacts on aquatic life. However, there have been few rigorous studies of cutting-edge technology used to eradicate XOCs and their presence in bathroom greywater. The present review provides a comprehensive examination of current methodologies used for removing XOCs by photocatalysis of green nanoparticles. It was appeared that zinc oxide nanoparticles (ZnO NPs) have high efficiency (99%) in photocatalysis process. Green synthesis provides proven processes that do not require dangerous chemicals or expensive equipment, making photocatalysis a potential solution for the status quo. XOCs residue was decomposed, and pollutants were eliminated with varied degrees of efficiency using green synthesis ZnO nanoparticles. It is hypothesized that the utilization of photocatalysis can create a greywater treatment system capable of degrading the toxic XOCs in greywater while increasing the pace of production. Hence, this review will be beneficial in improving greywater quality and photocatalysis using green nanoparticles can be an immediate platform in solving the issue regarding the existence of XOCs in greywater in Malaysia. Researchers in the future may benefit from focusing on optimizing photocatalytic degradation using green-synthesis ZnO. It might also help with the creativity and productivity of the next generation of authoritative concerns, notably water conservation.